Stress differentially affects the systemic and leukocyte estrogen network in common carp. Issue 68 (September 2017) - Szwejser, Ewa; Pijanowski, Lukasz; Maciuszek, Magdalena; Ptak, Anna; Wartalski, Kamil; Duda, Malgorzata; Segner, Helmut; Verburg-van Kemenade, B.M. Lidy; Chadzinska, Magdalena
Abstract: Both systemic and locally released steroid hormones, such as cortisol and estrogens, show immunomodulatory actions. This research gives evidence that circulating and leukocyte-derived estrogens can be involved in the regulation of the immune response in common carp, during homeostasis and upon restraining stress. It was found that stress reduced level of blood 17β-estradiol (E2) and down-regulated the gene expression of components of the "classical" estrogen system: the nuclear estrogen receptors and the aromatase CYP19, in the hypothalamus, the pituitary and in the ovaries. In contrast, higher gene expression of the nuclear estrogen receptors and cyp19a was found in the head kidney of stressed animals. Moreover, stress induced changes in the E2 level and in the estrogen sensitivity at local/leukocyte level. For the first time in fish, we showed the presence of physiologically relevant amounts of E2 and the substrates for its conversion (estrone – E1 and testosterone – T) in head kidney monocytes/macrophages and found that its production is modulated upon stress. Moreover, stress reduced the sensitivity of leukocytes towards estrogens, by down-regulation the expression of the erb and cyp19 genes in carp phagocytes. In contrast, era expression was up-regulated in the head kidney monocytes/macrophages and in PBLs derived from stressed animals. We hypothesize that, the increased expression of ERα, that was observed during stress, can be important for the regulation of leukocyte differentiation, maturation and migration. In conclusion, these results indicate that, in fish, the estrogen network can be actively involved in the regulation of the systemic and local stress response and the immune response. Highlights: Carp monocytes/macrophages can synthesize endogenous estrogens. In carp leukocytes, stress changes the estrogen synthesis capacity and responsiveness to estrogens. Leukocyte-derived estrogens and estrogen receptors participate in the regulation of the immune response of carp. The estrogen network is involved in the regulation of the systemic and local stress response in fish.